Harga, Brand Image, Dan Atribut Produk Serta Pengaruhnya Terhadap Keputusan Pembelian Smartphone Berbasis Android - Siti Maryama; Yayat Sujatna (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2016)
The purpose of this study is to: (1) analyze the influence of brand image on purchase decisions android smartphone; (2) analyze the effect of price on purchase decisions android smartphone; and (3) analyze the influence of product attributes on purchase decisions android smartphone; (4) analyzing the influence of brand image, price, and product attributes together on purchasing decisions android smartphone. The method used is descriptive-quantitative. Place of research on campus of STIE Ahmad Dahlan Jakarta with a sample of the regular students majoring in management and accounting. Slovin sample is determined by the formula. The research variables teridiri of Price, Brand Image, Product Attribute, and Purchase Decision. Analysis technique using classical assumption, F test, t test. Previous research instruments testing using validity and reliability test. The results of these empirically concluded that: (1) the price sginifikan influence on purchasing decisions android smartphone; (2) brand image significantly influence purchasing decisions android smartphone; (3) product attributes significantly influence purchasing decisions android smartphone; and (4) the fourth brand image, price, and product attributes together significantly influence purchasing decisions android smartphone. The posibble reason are discussed in this article.